Immersion in the Profession: Experience of Career Guidance Work at Medical University - P. V. Tkachenko; S. V. Cherney; E. А. Kovaleva (Высшее образование в России)
Higher medical education places high demands to the quality of applicants’ knowledge, assumes the awareness of their choice of future profession. As practice shows, often this choice is made by high school students at the level of momentary desires, current hobbies, intuition or under the pressure of social stereotypes, parents, teachers or friends. Not having a full understanding of the specifics and functional content of the chosen profession, they eventually become disillusioned with the chosen profession and lose all interest in it. Modern requirements to the preparation of medical personnel put forward the need to improve the methods of career guidance and close interaction of universities with the population, authorities and health management. The purpose of career guidance at medical university is the formation of good-quality contingent of students for the preparation of qualified medical personnel taking account of the needs of the regions. The University tries to assist youth in professional self-determination, development, social and psychological adaptation, future work.The article summarizes the experience of Kursk State Medical University in career guidance in medical school, offers a model aimed at improving the professional orientation of young people. This model assumes professional immersion at the pre-University, University and postgraduate stages of work. Professional immersion allows to realize multistage professional formation, to estimate risks, to see difficulties and to outline points of application of personal efforts. By means of professional immersion it is possible to attract to medical work the most prepared youth having a medical orientation, steady motivation to future professional activity, possessing the necessary level of professionally important qualities. The effectiveness of the proposed model is confirmed by high rates of students’ satisfaction with the content of education, studying at the University, and future profession.